A genome-wide analysis of antimicrobial effector genes and their transcription patterns in Manduca sexta. (July 2015) - He, Yan; Cao, Xiaolong; Li, Kai; Hu, Yingxia; Chen, Yun-ru; Blissard, Gary; Kanost, Michael R.; Jiang, Haobo
Abstract: Antimicrobial proteins/peptides (AMPs) are effectors of innate immune systems against pathogen infection in multicellular organisms. Over half of the AMPs reported so far come from insects, and these effectors act in concert to suppress or kill bacteria, fungi, viruses, and parasites. In this work, we have identified 86 AMP genes in the Manduca sexta genome, most of which seem likely to be functional. They encode 15 cecropins, 6 moricins, 6 defensins, 3 gallerimycins, 4 X-tox splicing variants, 14 diapausins, 15 whey acidic protein homologs, 11 attacins, 1 gloverin, 4 lebocins, 6 lysozyme-related proteins, and 4 transferrins. Some of these genes ( e.g . attacins, cecropins) constitute large clusters, likely arising after rounds of gene duplication. We compared the amino acid sequences of M. sexta AMPs with their homologs in other insects to reveal conserved structural features and phylogenetic relationships. Expression data showed that many of them are synthesized in fat body and midgut during the larval-pupal molt. Certain genes contain one or more predicted κB binding sites and other regulatory elements in their promoter regions, which may account for the dramatic mRNA level increases in fat body and hemocytes after an immune challenge. Consistent with these strong mRNA increases, many AMPs become highly abundant in the larval plasma at 24 h after the challenge, as demonstrated in our previous peptidomic study. Taken together, these data suggest the existence of a large repertoire of AMPs in M. sexta, whose expression is up-regulated via immune signaling pathways to fight off invading pathogens in a coordinated manner. Graphical abstract: Structural model of Manduca sexta attacin-1. Phylogenetic relationships of defensin-related proteins/domains in M. sexta . Shift of AMP gene transcription in midgut between larval feeding and wandering stages. Logo of κB motifs with 0 and 1 mismatch in M. sexta AMP genes. Highlights: Identified 86 immune effector genes encoding 11 attacins, 15 cecropins, 24 defensin homologs, etc. Analyzed their structural features, evolutionary relationships, and expression profiles. Correlated immune inducibility of mRNAs and proteins with putative regulatory elements in the genes.